Adaptation Of Disruption In Fast Food Companies In The New Normal Era - Rinintha Parameswari; Pujiarti Pujiarti; Eso Hernawan (Fakultas Bisnis, 2020)
The purpose of this research is how the community can adapt to the changes that occur in fast food companies in the new normal era. Discipline and public understanding of changes during the pandemic and entering the normal era are very important from habituation and technology. This research is descriptive by collecting primary data and also secondary data by conducting analysis and random interviews with services on fast food, visitors, and other data. This observation was made because fast food is the food most often consumed by people around> 80% because it is fast in providing it and this food is the people's choice for holding meetings both formal and informal. The results obtained and analyzed for this new order of life by opening it up gradually and getting used to the conditions applied by the government since March until now have made people accustomed to the existence of temperature checking regulations, wearing masks, maintain distance and determine other health protocols. With the existence of health rules applied the community has realized the importance of maintaining health even with meetings with others. The use of cashless or delivery that was already available in service applications before the pandemic and some people can already use it but others are more accustomed to using other merchant applications because it is considered easier and the number of choices and discounts.